KEMAMPUAN KOMITMEN ORGANISASIONAL MEMODERASI PENGARUH KOMPENSASI DAN TEKANAN WAKTU PADA KEPUASAN KERJA AUDITOR - Wicaksono, Yohanes Berchmans Adi; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
The purpose of this study to determine the ability of organizational commitment as moderating compensation and the time pressures on job satisfaction auditor. The study population was 45 auditor of Public Accounting Firm (KAP) in Bali with purposive sampling criteria. Data have been tested and qualified classical assumption test, test the feasibility of this model, with a coefficient of determination of 74%, the analytical techniques used Moderated Regression Analysis (MRA) with real rates (?) of 0.05.The test results showed (1) variable time pressure positive and significant impact on job satisfaction auditor, (2) compensation does not affect the job satisfaction of auditors, (3) organizational commitment strengthen  the influence of compensation on job satisfaction auditor at KAP  province of Bali,  (4) a commitment organizational weaken  the influence of the time pressures on job satisfaction auditor at KAP in Bali.
Keywords: compensation, time pressure, organizational commitment, job satisfaction auditor